Results from the Fertilizer demonstration experiment with maize at IOP Farm in Iringa, Tanzania in 2019 - Mtakwa, Pete; Urio, Ndelilio A.; Mtakwa, Alpha Peter; Brentrup, Frank; Assey, Peter; Loon, Marloes P. van; Hijbeek, Renske; Berge, Hein F.M. ten; Ittersum, Martin van (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
In 2019, an experiment was run at the IOP farm in Tanzania. Five nutrient management treatments were combined in a full factorial setup with two tillage options. The lowest maize yield was obtained under conventional tillage without fertilizer application, and the highest maize yield with reduced tillage and the highest NPK fertilizer level combined with micronutrients. This highest NKP fertilizer level targeted 70% of water-limited yield. Furthermore, it was shown that P and K were used more efficient under reduced tillage compared to conventional tillage, while there was no difference in N use efficiency between the two tillage options. In addition, a number of field visits was organized. From the six villages surrounding the farm a total of 120 farmers made at least 4 visits to the experiment once in every month between February and June. That brings the number of farmers that learned from the 2018 trial to 480+.